Evaluation of Crack under the Small Scale Analysis of Flexural Member as Partial Replacement of Steel to Bamboo Reinforcement - et al., S.Karthik (International Journal of Advanced Science and Technology, 2019)
The research is based on a theoretical and practical demonstration of the crack pattern analysis of comprehensive use of bamboo as a reinforcing material in concrete construction and its extensive use in the substitution with steel as reinforcement in concrete load bearing members. The use of bamboo in the place of steel as a whole as well as steel is shown to ensure the reduction in weight, economic advantage with its strength compromised to a slight and safe level. Bamboo is divided into two major portions 1.Rhizomes, 2 .Culms. We are planned to adopt the natural material of bamboo as reinforcement in the replacement of steel with increasing percentage of bamboo from 25 %, 50 %, 75 % & 100 % in beam.